Proceedings of the Internet Measurement Conference 2018 2018
DOI: 10.1145/3278532.3278550
|View full text |Cite
|
Sign up to set email alerts
|

On the Origins of Memes by Means of Fringe Web Communities

Abstract: Internet memes are increasingly used to sway and manipulate public opinion. This prompts the need to study their propagation, evolution, and influence across the Web. In this paper, we detect and measure the propagation of memes across multiple Web communities, using a processing pipeline based on perceptual hashing and clustering techniques, and a dataset of 160M images from 2.6B posts gathered from Twitter, Reddit, 4chan's Politically Incorrect board (/pol/), and Gab, over the course of 13 months. We group t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
270
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(279 citation statements)
references
References 24 publications
4
270
1
4
Order By: Relevance
“…(de Lima et al 2018) also found that Gab is very politically oriented and users who abuse the lack of moderation disseminate hate. (Zannettou et al 2018b) perform a large scale measurement study of the meme ecosystem by introducing a novel image processing pipeline. Gab has substantially higher number of posts with racist memes.…”
Section: Related Workmentioning
confidence: 99%
“…(de Lima et al 2018) also found that Gab is very politically oriented and users who abuse the lack of moderation disseminate hate. (Zannettou et al 2018b) perform a large scale measurement study of the meme ecosystem by introducing a novel image processing pipeline. Gab has substantially higher number of posts with racist memes.…”
Section: Related Workmentioning
confidence: 99%
“…Other. Zannettou et al [53] perform a study of meme evolution and propagation across different platforms, e.g. Twitter, Reddit, 4chan and Gab, where the last two are image boards structurally similar to Reddit.…”
Section: From the Perspective Of Postsmentioning
confidence: 99%
“…Across the globe, individuals are skeptical of traditional media vehicles and growingly consume news and opinion content on social media [22,31]. In this setting, recent research has shown that fringe websites (like 4chan) and subreddits (like /r/TheDonald) have great influence over which memes [44] and news [45] are shared in large social networks, such as Twitter. YouTube is extremely popular, especially among children and teenagers [7], and, if the streaming website is actually radicalizing individuals, this can push fringe ideologies like white supremacy further into the mainstream [42].…”
Section: Introductionmentioning
confidence: 99%